Performance of turbo coded triply-Polarized MIMO–CDMA system for downlink communication. (November 2016) - Karthipan, R.; Vishvaksenan, K.S.; Kalidoss, R.; Krishan, Anjana
Highlights: We investigate the BER performance of turbo coded MIMO–CDMA system using polarization diversity for DL transmission. Performance is analyzed using MMSE/OSIC algorithm when communicating over SUI and LTE channel models specifications. BER Performance of turbo -coded MIMO system is compared with uncoded system and Found that coded system provides superior performance. Our considered coded triply-Polarized MIMO–CDMA system achieves higher data rate with reduced size of Mobile unit. Abstract: In this paper, the performance of a turbo coded, triply-Polarized multiple-input multiple-output (MIMO) aided Code Division Multiple Access (CDMA) is investigated for Stanford University Interim (SUI) and Long-term Evolution (LTE) channel model specifications. The minimum mean square error algorithm based on ordered successive interference cancellation (OSIC) Multi-user detection (MUD) technique is implemented at each mobile station for diminishing the effects of multi-stream interference (MSI). We observe from the simulation results that a better bit error rate(BER) performance with less signal to noise ratio (SNR), is exhibited by our considered coded system in comparison with an un-coded system. The simulation results reveal that the MIMO–CDMA system with triply-Polarized antenna structure requires a higher SNR than a uni-Polarized antenna system for achievement of the same BER. However, it provides the advantage of replacement of three uni-polarized antennas by a single triply-Polarized antenna thereby achieves a higher data rate with reduced size of MS. Graphical abstract: